RUMAH EDUKATIF SEBAGAI UPAYA RESILIENSI BIDANG PENDIDIKAN DI DESA ROWOREJO, KABUPATEN KEBUMEN - Ahmad Sofyan Fauzi; M. Rosyid Irfan A (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2022)
Education is a right that must be obtained by all humans without exception. In its implementation, education consists of various important elements such as teachers, students, parents, and facilitators in the field of education. However, in reality, the implementation of educational activities is often found obstacles that hinder the fulfillment of educational needs. During the current COVID-19 pandemic, the pandemic has become a major obstacle in implementing it. Another problem related to the implementation of educational activities is the uneven accessibility in several regions in Indonesia. One area that is currently experiencing these two obstacles is Roworejo Village, Kebumen Regency, Central Java. Using a qualitative descriptive method, this study will look for the right method for the Roworejo village community in stabilizing their education sector and implementing a solution in the form of "Educational Houses" for the continuity of educational activities in the village area.